Factors related to Hb-Var in maintenance hemodialysis patients - XIAO Xiao-fen; HUANG Hai-ming; WANG Xiao-qin (Linchuang shenzangbing zazhi)
Objective To investigation and analysis the hemoglobin variability(Hb-Var) of maintenance hemodialysis(MHD) patients in the Hubei Provincial Hospital of Traditional Chinese Medicine and explore the factors related to Hb-Var.Methods The study enrolled 56 MHD patients in the Blood Purification Center,Hubei Provincial Hospital of Traditional Chinese Medicine between December 2013 and June 2014.Demographics and characteristics at baseline were collected.The doses of erythropoietin stimulating agents(ESAs) and intravenous doses of iron,and the number of adjusting ESAs,hemodiafiltration(HDF) and hemoperfusion(HP) were recorded during a follow-up period of 6months.The laboratory parameters including hemoglobin(Hb),calcium(Ca),phosphorus(P),immunoreactive parathyroid hormone(iPTH),serum ferritin(SF),and albumin(Alb) were determined at least three times during the follow-up period of 6 months.The Hb-Var was described by Hb coefficient of variation(Hb-CV) and fluctuation across threshold of the Hb level.The factors related to HbVar were analyzed.Results(1)There were 43 patients in the groups of Hb amplitude,accounting for76.79%;(2)Hb-CV was significantly different in gender,age,age of hemodialysis,vascular access for hemodialysis,dose of intravenous iron,and the number of adjusting ESAs(P<0.05);(3)Pearson correlation analysis revealed that Hb-CV was positively correlated with dose of the number of adjusting ESAs(r=0.757,P<0.05) and dose of intravenous iron(r= 0.757,P<0.05),but negatively with age of hemodialysis(r=-0.323,P<0.05),serum ferritin(r=-0.390,P<0.05) and albumin(r =-0.418,P<0.05),but not with age,calcium,phosphorus and immunoreactive parathyroid hormone;(4) Multiple regression analysis revealed that gender,vascular access for hemodialysis,the number of adjusting ESAs,dose of intravenous iron,and SF were independently associated with HbCV.Conclusions Hb-Var occurs commonly in maintenance hemodialysis patients,and it may be more obvious in the older.Fluctuation of Hb levels is closely associated with gender,vascular access for hemodialysis,and dose of intravenous iron.However,the relationship between Hb-Var and prognosis of CKD is still controversial,which needs more studies.